Improved grey wolf optimizer for optimal reactive power dispatch with integration of wind and solar energy - Laouafi, F. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The aim of this paper is to present a new improved grey wolf optimizer (IGWO) to solve the optimal reactive power dispatch (ORPD) problem with and without penetration of renewable energy resources (RERs). It is a nonlinear multivariable problem of optimization, with multiconstraints. The purpose is to minimize real power losses and improve the voltage profile of a given electric system by adjusting control variables, such as generator voltages, tap ratios of a transformer, switching VAr sources, without violating technical constraints that are presented as equalities and inequalities. Methodology. Metaheuristics are stochastic algorithms that can be applied to solve a wide variety of optimization problems without needing specific problem structure information. The penetration of RERs into electric power networks has been increased considerably to reduce the dependence of conventional energy resources, reducing the generation cost and greenhouse emissions. It is essential to include these sources in power flow studies. The wind and photovoltaic based systems are the most applied technologies in electrical systems compared to other technologies of RERs. Moreover, grey wolf optimizer (GWO) is a powerful metaheuristic algorithm that can be used to solve optimization problems. It is inspired from the social hierarchy and hunting behavior of grey wolves in the wild. The novelty. This paper presents an IGWO to solve the ORPD problem in presence of RERs. Methods. The IGWO based on enhancing the exploitation phase of the conventional GWO. The robustness of the method is tested on the IEEE 30 bus test system. For the control variables, a mixed representation (continuous/discrete), is proposed. The obtained results demonstrate the effectiveness of the introduced improvement and ability of the proposed algorithm for finding better solutions compared to other presented methods.

Метою статті є представлення нового покращеного оптимізатора сірого вовка (IGWO) для вирішення задачі оптимального розподілу реактивної потужності (ORPD) із застосуванням відновлюваних джерел енергії (RERs) та без них. Це нелінійне багатовимірне завдання оптимізації з безліччю обмежень. Мета полягає в тому, щоб мінімізувати реальні втрати потужності і покращити профіль напруги заданої електричної системи шляхом регулювання змінних керуючих, таких як напруги генератора, коефіцієнти відгалужень трансформатора, перемикання джерел реактивної потужності, не порушуючи технічних обмежень, які представлені у вигляді рівностей і нерівностей. Методологія. Метаевристика – це стохастичні алгоритми, які можна застосовувати для вирішення широкого спектра задач оптимізації без необхідності конкретної інформації про структуру проблеми. Проникнення RER в електромережі значно зросла задля зниження залежності від традиційних джерел енергії, зниження вартості генерації та викидів парникових газів. Вкрай важливо включити ці джерела до дослідження потоків потужності. Системи на основі вітру та фотоелектрики є найбільш застосовуваними технологіями в електричних системах порівняно з іншими технологіями RERs. Більш того, оптимізатор сірого вовка (GWO) – це потужний метаевристичний алгоритм, який можна використовувати для розв’язання оптимізації задач. Він натхненний соціальною ієрархією та мисливською поведінкою сірих вовків у дикій природі. Новизна. У цій статті представлено IGWO для вирішення проблеми ORPD при наявності RERs. Методи. IGWO, заснований на покращенні фази експлуатації звичайного GWO. Надійність методу перевірена на тестовій системі шини IEEE 30. Для керуючих змінних запропоновано змішане уявлення (безперервне/дискретне). Отримані результати демонструють ефективність введеного покращення та здатність запропонованого алгоритму знаходити кращі рішення порівняно з іншими методами.
Keywords: optimal reactive power dispatch; renewable energy resources; wind energy; solar energy; improved grey wolf optimizer; оптимальний розподіл реактивної потужності; відновлювані джерела енергії; енергія вітру; сонячна енергія; покращений оптимізатор сірого вовка